Screening of soybean genotypes for antixenosis against Spodoptera litura: Screening of soybean genotypes for antixenosis against Spodoptera litura - VANGALA RAJESH; LOKESH KUMAR MEENA; SANJAY GUPTA; M SHIVAKUMAR; V NATARAJ; VIRAJ G KAMBLE; R RAMTEKE; SUBHASH CHANDRA; R N SINGH; A N SHARMA (Journal of Oilseeds Research, 2020)
Among 95 soybean genotypes screened against Spodoptera litura, 2 genotypes viz., Hara Soya and G5P22 exhibited strong antixenosis, 11 genotypes exhibited moderate antixenosis. Whereas, 40 genotypes and 42 genotypes expressed slight antixenosis and preference host respectively.